The Virtual Fields Method Extracting Constitutive Mechanical Parameters from Full-field Deformation Measurements - Pierron, Fabrice; Grédiac, Michel (Springer New York : Imprint: Springer, 2012)
The Virtual Fields Method: Extracting Constitutive Mechanical Parameters from Full-field Deformation Measurements is the first book on the Virtual Fields Method (VFM), a technique to identify materials mechanical properties from full-field measurements. Firmly rooted with extensive theoretical description of the method, the book presents numerous examples of application to a wide range of materials (composites, metals, welds, biomaterials) and situations (static, vibration, high strain rate). The authors give a detailed training section with examples of progressive difficulty to lead the reader to program the VFM and include a set of commented Matlab programs as well as GUI Matlab-based software for more general situations. The Virtual Fields Method: Extracting Constitutive Mechanical Parameters from Full-field Deformation Measurements is an ideal book for researchers, engineers, and students interested in applying the VFM to new situations motivated by their research.  .